Integration of generative machine learning with the heuristic crystal structure prediction code FUSE - Collins, Christopher M; Sayeed, Hasan M; Darling, George R; Claridge, John B; Sparks, Taylor D; Rosseinsky, Matthew J (Faraday discussions, 2025)
The prediction of new compounds via crystal structure prediction may transform how the materials chemistry community discovers new compounds. In the prediction of inorganic crystal structures there are three distinct classes of prediction: performing crystal structure prediction via heuristic algorithms, using a range of established crystal structure prediction codes, an emerging community using generative machine learning models to predict crystal structures directly and the use of mathematical optimisation to solve crystal structures exactly. In this work, we demonstrate the combination of heuristic and generative machine learning, the use of a generative machine learning model to produce the starting population of crystal structures for a heuristic algorithm and discuss the benefits, demonstrating the method on eight known compounds with reported crystal structures and three hypothetical compounds. We show that the integration of machine learning structure generation with heuristic structure prediction results in both faster compute times per structure and lower energies. This work provides to the community a set of eleven compounds with varying chemistry and complexity that can be used as a benchmark for new crystal structure prediction methods as they emerge. We integrate generative machine learning with heuristic crystal structure prediction in FUSE. The combined result shows superior performance over both components, accelerating the pace at which we will be able to predict and discover new compounds.